Antidiabetic activity of the leaves of tetracera indica merr. (Dilleniaceae) in vivo and in vitro - Ahmed, Qamar Uddin; Taher, Muhammad (Academic Journals, 2012)
In folk remedies, the leaves of Tetracera indicaare used to treat diabetes in Malaysia. This study was aimed at investigating the antidiabetic potential of T. indica leaves in vivo and in vitro to prove its usefulness in diabetes. Aqueous (AQ) and methanol (MEOH) extracts of T. indica leaves were administered to normal and alloxan induced diabetic male albino rats (Sprague Dawley strain). Two doses of each extract (250 and 500 mg/kg B.W) were evaluated for antidiabetic activity in vivo. The blood glucose levels were measured at 0, 2, 4, 6 and 8 h after oral administration of extracts. Comparison was made with glibenclamide (GLBC). For the in vitro method, the effect of both extracts on the lipid accumulation of 3T3-L1 adipocytes was analyzed by using Oil Red O staining. In addition, 2- deoxy-D-[3H] was used to measure the effect of the extracts on glucose uptake activities. Both extracts exhibited antihyperglycemic activity in alloxan induced diabetic rats, however in normal rats no hypoglycemic activity was observed, when compared with both +ve and -ve controlled groups. The LD50 of both extracts was found to be more than 5000 mg/kg body weight and no lethal toxicity was observed within this range. For in vitro analysis, AQ extract was found to reduce triglyceride accumulation on 3T3-L1 cells in a dose-dependent manner whereas cells treated with MEOH extract significantly induced lipid accumulation. Besides, 2-deoxy-D-[3H] glucose uptake activities were significantly different at dose 200 μg/mL (P < 0.05 compared to DMSO control). Moreover, the data were significant (P > 0.05) with MDI (inducer) and metformin which were used as the positive control for the in vitro assay.